基于有限元模拟的谐波传动中齿干涉分析 - 余光辉; 谭晶; 黄迪山 (Jixie chuandong)
The tooth interference caused by the cup-shaped flexspline deformation is analyzed with the finite element method.Using UG software to build 3D models of the elliptical cam wave generator,the cup-shaped flexspline and the rigid gear,the models are imported to the ANSYS finite element software by Parasolid format and analyzed.The Node-Surface contact element to solve the contacting problem between the flexspline and the wave generator is put forward,so that the deformed flexspline is more approximate to the actual working conditions.Under no load condition,by taking the deformed cup-shaped flexspline as the object,the tooth interference caused by the radial displacement and the circumferential displacement is analyzed,and a method to observe the phenomenon of the tooth interference is proposed,and it provides a reference to the optimization for the harmonic drive.